Altered Topological Organization in the Sensorimotor Network After Application of Different Frequency rTMS - Wei, Wei; Zhu, Tingting; Wang, Xiaoyu; Li, Lingyu; Zou, Qihong; Lv, Yating (Frontiers in Neuroscience, 2019)
The application of repetitive transcranial magnetic stimulation (rTMS) over the primary motor cortex (M1) could influence the intrinsic brain activity in the sensorimotor network. However, how rTMS modulates the topological organization of the sensorimotor network remains unclear. In this study, we employed resting-state fMRI to investigate the topological alterations in the functional sensorimotor network after application of different frequency rTMS over the left M1. To accomplish this, we collected MRI data from 45 healthy participants who were randomly divided into three groups based on rTMS frequency (HF, high-frequency 3 Hz; LF, low-frequency 1 Hz; and SHAM). Individual large-scale functional sensorimotor networks were constructed by correlating the mean time series among 29 regions of interest in the sensorimotor network and were fed into graph-based network analyses at multiple levels of global organization and nodal centrality. Our results showed that compared with the network metrics before rTMS stimulation, the left paracentral lobule (PCL) exhibited reduced nodal degree and betweenness centrality in the LF group after rTMS, while the right supplementary motor area (SMA) exhibited reduced nodal betweenness centrality in the HF group after rTMS. Moreover, rTMS-related alterations in nodal metrics might have been attributable to the changes in connectivity patterns and local activity of the affected nodes. These findings reflected the potential of using rTMS over M1 as an effective intervention to promote motor function rehabilitation.